Inventário Estruturado de Aranhas (Arachnida, Araneae) em uma Área de Várzea do Rio Guamá, Belém, Pará, Brasil - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2004)
Spiders are distributed in 39725 species described in 3677 genera worldwide. Structured inventories of spiders are still very rare in the Amazon, especially in the Eastern Amazon, and the present study will contribute to the knowledge of the spider fauna in the region. The objective of this work was to promote a structured inventory of the spider fauna and to make diversity analyses in the sampling area, besides providing data to evaluate the biological diversity, generating subsidies for future conservation plans of the studied ecosystem. Collections were made in an area of floodplain of the Guamá River, within the campus of the Federal University of Pará, near the city of Belém, in December 2006 and April 2007. The technique used to obtain the samples was the entomological umbrella, which consists in the capture of diurnal arboreal animals in forest and shrub strata up to two meters high. The sampling effort resulted in 64 samples where 2942 individuals belonging to 28 families were collected, of which 822 individuals are adults and 2116 are juveniles. The families Theridiidae (728 individuals), Araneidae (619 individuals), Pisauridae (424 individuals) and Salticidae (390 individuals) were the most abundant in the area, representing together more than 70% of all spiders collected. These families also had the highest frequency of young individuals, representing 73% of the total number of young. To date, individuals have been identified to the family level, and are being identified 'to the more specific taxonomic level where possible. The final product of the specific identification of the spider fauna will be the construction of an incidence/abundance matrix that will be used in diversity analyses.
Structured Inventory of Spiders (Arachnida, Araneae) in a River Guamá Floodplain Area, Belém, Pará, Brazil
Keywords: Inventário estruturado; Análises de diversidade; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES